Qualitative Study on Stigma and Discrimination Against PLWHA in Urban Communities - Yumi Abimulyani; Pius Weraman; Zuhrotunida Zuhrotunida; Andi Subhan Amir (PT. Anagata Sembagi Education, 2025)
Stigma against people living with HIV/AIDS (PLWHA) in urban communities continues to be a significant issue despite advances in information and health services. Although better access to information can reduce prejudice, negative myths and stereotypes about HIV remain deeply rooted in society. This study reveals how stigma against PLWHA in large cities in Indonesia is influenced by moral narratives that associate HIV with deviant behavior, exacerbating unfounded fears about transmission. Limited knowledge about how HIV is transmitted, as well as often sensationalist media representations, further reinforce social discrimination against PLWHA. In addition to explicit discrimination, structural discrimination in the health sector and the workplace worsens the living conditions of PLWHA, hinders access to medical care and exacerbates socio-economic inequalities. This study uses a qualitative approach with a literature review to explore the social construction of stigma and discrimination against PLWHA in urban areas. Through thematic analysis of various secondary sources, it is found that a more inclusive and culturally based approach is needed to address stigma, including campaigns that actively involve the community and improve more equitable policies. These findings contribute to a deeper understanding of stigma as well as recommendations for public policies that are more oriented towards social justice and human rights for PLWHA.